Introduction to Polar Law - Scott K; VanderZwaag D (Edward Elgar, 2021)
This introductory Chapter identifies the key questions that frame the fast-changing arena of Polar Law and which set the tone and parameters of this Research Handbook. The most fundamental question is ‘what is “Polar Law”’? In attempting to answer this question, we engage with the issue of how to define and describe the Poles before going on to articulate two possible definitions of Polar Law. In developing the first definition, we ask whether we can readily and clearly identify a set of rules and principles that apply to the Polar regions. In articulating a second, more challenging definition, we ask whether it is possible to identify a body of rules and principles that apply coherently across both Poles based on common values. Given the acknowledged challenges of this exercise, we go on to briefly ask whether we need Polar—rather than Arctic and Antarctic—law and draw some preliminary conclusions as to the benefits of a Polar rather than a bipolar approach. Finally, we examine a selection of the challenges to Polar Law, a theme which is taken up in detail by all authors in this Research Handbook across the various areas identified above.